Effect of Ultrasound Guided Rectus Sheath Block on Postoperative Analgesia after Laparotomy with Transverse Incision in Children - Aydin Halefoglu (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: Rectus sheath block have been used for postoperative pain control in adult patients undergoing abdominal surgery. To investigate the effect of the ultrasound guided rectus sheath block (RSB) with levobupivacaine on both intraoperative sevoflurane consumption and postoperative analgesia after laparotomy with transverse incision in children. Material and Methods: Forty patients with ASA I-II physical status, aged 3-7 years and undergoing laparotomy with transverse incision were randomly allocated into two groups. Patients were administered general anesthesia and before the beginning of surgery ultrasound guided RSB with 0.2 mL/kg, 0.25% of levobupivacaine and thirty minutes before the surgery the loading dose of morphine of 0.1 mg/kg intravenously were received in group RSB and group M, respectively. Analgesic drug pump with 0.01 mg/kg bolus doses of morphine and 30 minutes lockout interval was set up postoperatively in both groups. Concentrations (%) and consumed amounts (mL/h) of sevoflurane during the surgery and systolic and diastolic blood pressure, heart rate, and peripheral oxygen saturation values were recorded both intraoperative and postoperative period in each groups. Analgesic consumption with postoperative analgesic drug pump, FLACC pain scores, sedation level, nausea, vomiting, supplemental analgesic requirement and side effects were also recorded. Results: Demographic data and hemodynamic parameters were similar in both groups excepting that systolic arterial pressure values were reduced in group RSB than in group M. Inhaled concentration and consumed amounts of sevoflurane were decreased in group RSB compared with group M. Averages of consumptions of sevoflurane were 18.7+/-2.1 mL/h and 21.5 +/-2.9 mL/h in group RSB and group M, respectively (p<0.001). Postoperative FLACC scores, sedation scores, and morphine consumption for 24 hours were lower in group RSB than in group M (p<0.001). Three patients had nausea in group M, however no nausea and vomiting was observed in group RSB and any patients did not need supplemental analgesia postoperatively. Conclusions: Ultrasound guided RSB is superior to intravenous morphine according to intraoperative anesthetic gas consumption and postoperative pain control in children undergoing abdominal surgery using transverse incision. [Cukurova Med J 2015; 40(3.000): 534-541]